Differences and Relationship Between Attitudes and Self Efficacy of Female and Male Students in Science Subjects in Junior High School - Retni Sulistiyoning Budiarti; Dwi Agus Kurniawan*; Sabila Eka Septi; Rahmat Perdana (Jurnal Pendidikan Sains Indonesia, 2022)
Students' attitudes and self-efficacy are very important in science subjects. With a good attitude and self-efficacy, learning will be easier and more enjoyable. This study aims to examine the attitudes and self-efficacy of female and male students from two classes, namely VII A and VII B in junior high school. This research is a type of quantitative survey research. The sampling technique used in this study was simple random sampling with the research subjects as many as 74 junior high school students studying science. The instrument used in data collection was 28 questions containing 5 choices that must be filled out by students. Analysis of the data used in this study in the form of descriptive analysis and T test and correlation test to determine whether there is a comparison and relationship between students' attitudes and efficacy towards science. The results obtained indicate that there are significant differences and relationships between attitudes and self-efficacy of female and male students. These results indicate that male students have an average attitude and good self-efficacy compared to female students at the junior high school level